Monitoring the impact of COVID-19 in Myanmar: Yangon peri-urban poultry farmers - November 2020 survey round - Fang, Peixun; Belton, Ben; Ei Win, Hnin; Zhang, Xiaobo (International Food Policy Research Institute, 2020)
Poultry farmers in Myanmar were interviewed by telephone in early June, late June, early July, late July, and August 2020 to determine how their businesses were being affected by COVID-19 related restrictions. The results of those surveys were published in Myanmar Strategy Support Program Policy Notes 11, 13, 19, 21, and 28, respectively. To trace the continuing impact of the COVID-19 pandemic on their economic activities, a sixth round of the phone survey of poultry farmers was done in November 2020. The sixth round sample included 226 poultry farmers (162 broiler and 64 layer farms) in the Yangon peri-urban area (Ayeyarwady, Bago, and Yangon regions) who had been interviewed in the first five rounds of the survey. The same survey questionnaire was used. This survey round is three months after the August survey round, so most broiler farms should have finished a full production cycle between the two last survey rounds. This Policy Note reports on the results of this sixth survey round.